The Impact of Personality Types on Aggressive Behavior in Juvenile Delinquents in Shelters - Al Khateeb, Sahar Hussien; Khlifat, Mostafa Ali; Almajali, Hussein Khazer; alshamayleh, Zaid Mahmood (Journal of Ecohumanism, 2024)
The study aimed to identify the impact of personality types on aggressive behavior among juvenile delinquents in shelters, and determine if there are differences attributable to the variables of gender and educational level. To achieve the objectives of the study, a questionnaire was constructed consisting of three parts; the first part included personal information about the respondents; the second was related to personality types (introversion, emotionality, extraversion) and contained (15) items; the third was related to aggressive behavior (against oneself, others, and objects) and contained (27) items. The study sample was selected using the comprehensive listing, which consisted of (150) juvenile delinquents who were kept in both the Osama bin Zeid Shelter and the Shelter of education and rehabilitation for Girls / Al-Rusaifah. The results showed that the arithmetic means of the personality types characteristic of juvenile delinquents ranged between (2.38-3.79), where the extroversion type came first, followed by the emotionality type, while the introversion pattern came last. As for the aggressive behavior patterns of juveniles, the results showed that the domain of aggressive behavior against others came first, followed by aggressive behavior against objects, while the domain of aggressive behavior against oneself came last. The results also showed that there are no statistically significant differences that are attributed to the variables of the gender and educational level of the sample members in all personality types, as the results showed that there is a statistically significant negative relationship between extroversion and aggressive behavior against oneself, as well as introversion and aggressive behavior against others. However, there is a positive relationship between extroversion and aggressive behavior against others, introversion and aggressive behavior against oneself, emotionality and aggressive behavior against others and against objects.